2013
DOI: 10.1063/1.4808204
|View full text |Cite
|
Sign up to set email alerts
|

Theory of magnetoelectric effect in multilayer nanocomposites on a substrate: Resonant bending-mode response

Abstract: Resonant bending-mode magnetoelectric (ME) coefficients of magnetostrictive-piezoelectric multilayer cantilevers are calculated analytically using a model developed for arbitrary multilayers on a substrate. Without quality factor effects the ME coefficient maxima in the four-dimensional parameter space of layer numbers, layer sequences, piezoelectric volume fractions, and substrate thicknesses are found to be essentially constant for nonzero substrate thickness. Global maxima occur for bilayers without substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Recently near bulk piezoelectric properties were achieved for 10nm AlN. 42 The open circuit results 36,37 and corresponding neutral plane behavior are briefly reiterated here. Minima regions producing primary and secondary maxima of the ME response are observed only in the layer sequences with functional materials at the central layer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently near bulk piezoelectric properties were achieved for 10nm AlN. 42 The open circuit results 36,37 and corresponding neutral plane behavior are briefly reiterated here. Minima regions producing primary and secondary maxima of the ME response are observed only in the layer sequences with functional materials at the central layer.…”
Section: Resultsmentioning
confidence: 99%
“…Low frequencies required for biomagnetic applications in medical diagnostic and imaging techniques (Magnetoencephalography, Magnetocardiography) have focused research on cantilever sensors using the resonance enhanced bending-mode magnetoelectric effect. [9][10][11]21,23 In recent papers [36][37][38] we investigated the static and resonant bending mode magnetoelectric effect in multilayer cantilevers of arbitrary layer number and different sequences on a substrate identifying optimized device geometries in a large multidimensional parameter space.…”
Section: Introductionmentioning
confidence: 99%
“…for free-free modes. Equations (15) and (16) are derived from the results for dQ dH using Eqs. (6) and (8) and additional calculation of dH dz at the cantilever tip x = a for the bound-free and free-free mode cases.…”
Section: Magnetic Field Detection Limitmentioning
confidence: 99%
“…[9][10][11][12][13] The results have encouraged investigations to enable the detection of weak low frequency biomagnetic fields with room temperature sensors. 14 This has involved research to increase the effect size of the ME response, e.g., materials, effects of device geometry and operation modes, [15][16][17][18] resonance-enhancement and loss mechanisms, 13 and investigation of noise effects and their behavior including the Johnson-Nyquist noise [19][20][21][22][23] from dielectric losses in piezoelectric materials 24 in ME cantilevers and electronics, noise in magnetostrictive (MS) materials, and thermal vibration noise. 23,[25][26][27][28] Different operation modes investigated for low frequency biomagnetic field sensing 14 include (1) direct detection, where magnetic fields oscillating at the cantilever resonance directly excite magnetostrictivepiezoelectric strain coupling and resonance-enhanced signals; (2) modulation techniques, [29][30][31] where signal fields are detected as sidebands to a carrier as a result of frequency mixing in non-linear functional materials; and (3) the ΔE effect, 32,33 where the field dependence of the elastic modulus in magnetostrictive materials is used.…”
Section: Introductionmentioning
confidence: 99%
“…Dai et al obtained the analytical solution of stresses in multilayer piezoelectric hollow structures [6]. Using a model of arbitrary multilayers on a substrate, Krantz and Gerken calculated the resonant bending-mode magnetoelectric (ME) coefficients of magnetostrictive-piezoelectric multilayer cantilevers, and it was found that ME coefficients strongly increase with cantilever thickness primarily due to increasing resonance frequencies [7]. An improved 1-D stress model for a single layer transformer in vacuum was used to model the multilayered transformer mounted on a printed circuit board, and a square pulse signal was amplified [8].…”
Section: Introductionmentioning
confidence: 98%